30 Years of TEFL/TESL: A Personal Reflection - Jack C Richards (TEFLIN, 2003)
This paper tries to answer eight questions, which are as follows. (1) What are the goals of teach English?; (2) What is the best way to teach a language?; (3) What is the role of grammar in language teaching?; (4) What processes are involved in second language learning?; (5) What is the role of the learner?; (6) How can we teach the four skills?; (7) How can we access students learner?; (8) How can we prepare language teachers?